DIELECTRIC PROPERTIES OF SOIL: A STUDY OF PARTICLE SIZE DISTRIBUTION AND MINERAL COMPOSITION (International Journal of Food and Nutritional Sciences, 2021)
This research paper investigates the dielectric properties of soil, focusing on the influence of particle size distribution and mineral composition. Dielectric properties, including dielectric constant and loss tangent, are critical for applications such as soil moisture sensing and geophysical surveys. The study presents a detailed analysis of how varying particle sizes—sand, silt, and clay—affect dielectric responses, showing that finer particles increase dielectric constants due to enhanced surface area and water retention. The impact of mineral composition is also examined, revealing that minerals like quartz and montmorillonite contribute differently to dielectric properties, with montmorillonite leading to higher dielectric constants compared to quartz. Empirical data from soil samples with different textures and mineral compositions underscore the complex interplay between these factors. Tables provide numerical data on dielectric constants for various soil types and minerals, illustrating the significant variations observed. Additionally, the study explores practical implications for soil analysis techniques, highlighting the need for calibration of dielectric sensors and accurate interpretation of geophysical data. The findings offer valuable insights for optimizing soil moisture measurement and improving the effectiveness of geophysical explorations, emphasizing the importance of considering both particle size and mineral composition in soil dielectric studies.